Permasalahan kesehatan dalam kondisi bencana: Peran petugas kesehatan dan partisipasi masyarakat - Widayatun; Fatoni, Zainal (Jurnal Kependudukan Indonesia, 2013)
Most Indonesian population are living in prone areas of natural disasters, including earthquake. Earthquake disasters followed by the long temporary shelters potentially create health problems; however, health systems in a disaster situation tend to face obstacles, such as the damaged or inadeaquate health existing facilities. This paper aims to discuss health problems following a disaster and to assess the role of health personnel and community participation in this situation. Data and information in this paper are mainly based on a study "Assessment on Basic Needs Fulfillment following Bantu/ Earthquake in 20016" and a desk review on related documents and literatures. The study found that within the health sector, many guidances indicate the important role of the health personnel during disaster situation. The 2006 Bantul Earthquake was not only resulting in number of deaths, injured people and the damaged health facilities, but it was also creating public health problems, for example the disaster related diseases, the broken water supply and sanitation facilities, traumatic issues among the victims and the limited access to the health reproductive services for women and couple. Health personnel together with community have essential role in dealing with disaster, from the initial stage following the earthquake (day 1-3), the emergency period (day 3-30) until the rehabilitation and recontruction phase (>1 month). Many factors contributed to the success story of the primary health care personnels in delivering publich health roles following the Bantul Earthquake, especially the actively community and volunteer participation in helping dealing with the disaster victims.